The Americans. Season 2 [videorecording (DVD)] - Russell, Keri, 1976-; Rhys, Matthew, 1974-; Emmerich, Noah (Twentieth Century Fox Home Entertainment, 2014)
Technological advances have escalated Cold War tensions to an all-time high, and undercover KGB operatives Elizabeth and Philip Jennings face the growing threat of discovery. As their assignments grow more deadly, their family is in more danger, and their loyalties are tested like never before.